PENGARUH LATAR BELAKANG KELUARGA, KEGIATAN PRAKTIK DI UNIT PRODUKSI SEKOLAH, DAN PELAKSANAAN PEMBELAJARAN KEWIRAUSAHAAN TERHADAP KESIAPAN BERWIRAUSAHA SISWA SMK DI KABUPATEN TANAH BUMBU - Emilda Jusmin (Jurnal Pendidikan Teknologi dan Kejuruan, 2012)
ABSTRACTThis study aims to investigate the effects of the family background, school production unit activities andlearning implementation of entrepreneurship on the entrepreneurship readiness of Vocational High School (VHS)students in Tanah Bumbu District, South Kalimantan.This study was an ex-post facto research applying the quantitative approach. The subjects were the studentsof public VHSs in Tanah Bumbu District South Kalimantan. The sample consisted of selected using the proportionalcluster random sampling technique. The data were collected using a four-scale Likert-type questionnaire. Theinstrument validity was assessed using the scale product moment correlation , while the instrument reliabilitywas assessed using the Cronbach’s Alpha formula. The techniques data analysis in this study were a descriptivetechnique and multiple regression at a significance level of 5%.The results of the multiple regression analysis are as follows. 1) There is a significant effect of the familybackground variable on the entrepreneurship readiness with a contribution of 19.3%. As many as 46.3% of thestudents have a family background in the low category. 2) There is a significant effect of the variable of school unitproduction activities on the entrepreneurship readiness of VHS students with a contribution of 21.7%. As manyas 40% of the students have school production unit activities in the low category. 3) There is a significant effect ofthe implementation of entrepreneurship teaching on the entrepreneurship readiness a contribution of 18.5 %. Asmany as 46.8% of the students have an entrepreneurial learning implementation in the low category. 4) There are asignificant effect of the family background variables, the school production unit activities, and the implementationof entrepreneurial learning as an aggregate with a contribution of 34.7%. As many as 42.9% of students haveentrepereneurship readiness in the low category.Keywords : Family Backgrounds, Shcool Production Unit Activities and Learning Implementation ofEntrepreneurship.